Computer-Aided Design and Computer-Aided Manufacturing for Pelvic Tumor Resection and Free Fibula Flap Reconstruction. Issue 4 (April 2020) - Agrawal, Nikhil; DeFazio, Michael V.; Bird, Justin E.; Mericli, Alexander F.
Abstract : Supplemental Digital Content is available in the text.